Swimming exercise changed the collagen synthesis and calcification in calcaneal tendons of mice - CARVALHO,ANGELA A. M. (2020)
Abstract Obesity is characterized by the excess of body fat and, therefore, may cause musculoskeletal alterations that can negatively influence the tendons. Such overweight-influenced alterations are exercise sensitive though. Morphological and biochemical alterations were reported in the calcaneal tendon of mice submitted to a lipid-rich diets along with practicing exercises, with the following groups: normal diet without exercise (ND), normal diet with exercise (NDex), lipid-rich diet without exercise (LD), lipid-rich diet without exercise (LDex). The calcaneal tendons were removed and subjected to histological and biochemical analysis. Layers of the tissue were stained with Hematoxylin and Eosin, Picrosirius Red and Von Kossa while a protein dosage was conduce by the Bradford method. The morphologicals analysis there was no statistical difference concerning the number of fibroblasts among the groups. Groups submitted to exercises showed higher amount of collagen and non-collagenous protein deposition. The lipid-rich diet without exercse group had a more disorganized collagen matrix with intense basophilia. The same group had areas of calcification confirmed by Von Kossa technique. Practicing physical activity, such as swimming, can improve the changes caused in the calcaneal tendon in mice submitted to a lipid-rich diets, having a better collagen organization and the synthesis.